Accuracy Patient Management in the Emergency Room: Social Cognitive Theory Insights - Parinding, Yunus; Indasah, Indasah; Puspitasari, Yenny (Jurnal Kesehatan, 2025)
Emergency healthcare services play a crucial role in patient survival, particularly in emergency departments (ED) where timely and accurate decision-making is vital. This study aims to analyze the personal, behavioral, and environmental factors that influence the accuracy of patient management in emergency departments, using the Social Cognitive Theory framework. An observational, cross-sectional study was conducted among 107 emergency nurses from all hospitals in Toraja, selected using total sampling. Independent variables included personal, behavioral, and environmental aspects, while the dependent variable was patient management accuracy. Data were collected using a validated questionnaire and analyzed through univariate, bivariate, and multivariate linear regression using statistical application. The study was approved by the Health Research Ethics Committee (Approval No: 0723419/EC/KEPK/I/05/2025). Results indicated an R-squared value of 0.502, suggesting that 50.2% of the variance in patient management accuracy could be explained by the three independent variables. Multivariate analysis revealed that the behavioral factor had the most significant influence (p=0.000; B=0.567). Behavioral factors play the most significant role in determining the accuracy of patient management in emergency departments, followed by environmental and personal factors. Strengthening clinical skills, teamwork, and adherence to protocols is essential to improving emergency care outcomes. Hospitals should prioritize continuous training, competency-based evaluations, and supportive work environments to enhance behavioral performance among emergency nurses. Future research is recommended to employ longitudinal designs to understand causal pathways better and to include broader healthcare roles beyond nursing.